2021
DOI: 10.6018/analesps.343041
|View full text |Cite
|
Sign up to set email alerts
|

Parental divorce, interparental conflict, and parent-child relationships in Spanish young adults

Abstract: El principal objetivo de este estudio fue analizar las asociaciones entre el divorcio parental y el conflicto interparental con la calidad de las relaciones paterno-filiales y materno-filiales, en una muestra española de 1078 adultos jóvenes. También se analizó la función moderadora del género de estos adultos jóvenes. Nuestros resultados sugirieron que el conflicto interparental se asocia con relaciones paterno-filiales y materno-filiales de menor calidad, mientras que el divorcio parental se asocia de forma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…Our data suggested that interparental conflict affects the relationship established by the adolescent with the father figure to a greater extent. There has been controversy in the literature about the differential impact of marital conflict on the relationship of the adolescent with his mother and father [ 22 , 23 , 24 , 25 , 26 ]. More evidence is available indicating that marital conflict equally affects the relationship with the mother and the father [ 23 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data suggested that interparental conflict affects the relationship established by the adolescent with the father figure to a greater extent. There has been controversy in the literature about the differential impact of marital conflict on the relationship of the adolescent with his mother and father [ 22 , 23 , 24 , 25 , 26 ]. More evidence is available indicating that marital conflict equally affects the relationship with the mother and the father [ 23 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been controversy in the literature about the differential impact of marital conflict on the relationship of the adolescent with his mother and father [ 22 , 23 , 24 , 25 , 26 ]. More evidence is available indicating that marital conflict equally affects the relationship with the mother and the father [ 23 , 25 , 26 ]. However, our results support those studies reporting that marital conflict affects the relationship with the father to a greater extent [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selain itu, perceraian menyebabkan perubahan signifikan dalam struktur keluarga dan dapat memengaruhi secara negatif terhadap ketersediaan fisik dan psikologis orang tua sebagai pengasuh utama (Feeney & Monin, 2016). Anak-anak dari keluarga yang bercerai dibesarkan dalam hak asuh bersama memiliki hubungan yang lebih baik dengan kedua orang tua dan terutama dengan ayah mereka, daripada ketika mereka dibesarkan dalam hak asuh tunggal, terutama ibu (Smith-Etxeberria & Eceiza, 2021). Dapat dilihat bahwa individu yang bercerai melaporkan lebih banyak masalah fisik seperti tekanan darah, masalah tidur, hingga memiliki tingkat kematian yang lebih tinggi dibandingkan dengan individu yang berpasangan atau masih single (Frisby et al, 2012).…”
Section: Pendahuluanunclassified